The find of COVID-19 vaccine: Challenges and opportunities - Marwan ElBagoury; Mahmoud M. Tolba; Hebatallah A. Nasser; Abdul Jabbar; Ahmed M. Elagouz; Yahia Aktham; Amy Hutchinson (Elsevier, 2021)
Severe acute respiratory syndrome coronavirus (SARS-CoV-2), a novel corona virus, causing COVID-19 with Flu-like symptoms is the first alarming pandemic of the third millennium. SARS-CoV-2 belongs to beta coronavirus as Middle East respiratory syndrome coronavirus (MERS-CoV). Pandemic COVID-19 owes devastating mortality and destructively exceptional consequences on Socio-Economics life around the world. Therefore, the current review is redirected to the scientific community to owe comprehensive visualization about SARS-CoV-2 to tackle the current pandemic. As systematically shown through the current review, it indexes unmet medical problem of COVID-19 in view of public health and vaccination discovery for the infectious SARS-CoV-2; it is currently under-investigational therapeutic protocols, and next possible vaccines. Furthermore, the review extensively reports the precautionary measures to achieve'' COVID-19/Flatten the curve''. It is concluded that vaccines formulation within exceptional no time in this pandemic is highly recommended, via following the same protocols of previous pandemics; MERS-CoV and SARS-CoV, and excluding some initial steps of vaccination development process.